2019
DOI: 10.1111/febs.14864
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the membrane lipid binding properties and lipase activity of Mycobacterium tuberculosis LipY domains

Abstract: The Mycobacterium tuberculosis LipY protein, a prototype of the proline‐glutamic acid (PE) family, exhibits a triacylglycerol (TAG) hydrolase activity that contributes to host cell lipid degradation and persistence of the bacilli. LipY is found either as a full‐length intracytosolic form or as a mature extracellular form lacking the N‐terminal PE domain. Even though the contribution of the extracellular form in TAG consumption has been partly elucidated, very little information is available regarding the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…Few years later, we reported that a new substitutive OX derivative, the MmPPOX (Figure 1), was also able to inhibit M. tb growth on solid medium with moderated MIC values of 50-90 µM [28]. We further showed that MmPPOX efficiently inhibited pure recombinant M. tb enzymes belonging to the hormone-sensitive lipase (HSL) family member proteins (i.e., Lip-HSL) [28], including LipY (Rv3097c) the major M. tb Lip-HSL lipase involved in TAG acquisition from the host and in ILI breakdown [2,10,17,41]. The mechanism of action of MmPPOX involving the formation of a covalent bond with the catalytic serine residue of the enzymes (Figure 1 inset) thus resulting in a total abolition of their activities was also confirmed [28].…”
Section: Mycobacterial Lipolytic Enzyme Inhibitors Are Promising Antituberculous Candidatesmentioning
confidence: 86%
“…Few years later, we reported that a new substitutive OX derivative, the MmPPOX (Figure 1), was also able to inhibit M. tb growth on solid medium with moderated MIC values of 50-90 µM [28]. We further showed that MmPPOX efficiently inhibited pure recombinant M. tb enzymes belonging to the hormone-sensitive lipase (HSL) family member proteins (i.e., Lip-HSL) [28], including LipY (Rv3097c) the major M. tb Lip-HSL lipase involved in TAG acquisition from the host and in ILI breakdown [2,10,17,41]. The mechanism of action of MmPPOX involving the formation of a covalent bond with the catalytic serine residue of the enzymes (Figure 1 inset) thus resulting in a total abolition of their activities was also confirmed [28].…”
Section: Mycobacterial Lipolytic Enzyme Inhibitors Are Promising Antituberculous Candidatesmentioning
confidence: 86%
“…The importance of GlfH1 in cell wall remodeling is further emphasized by its genomic environment, as it is adjacent to Rv3097c, also known as lipY, that encodes a wellcharacterized PE protein expressing triacylglycerol (TAG) hydrolase activity. LipY participates to consumption and reprocessing of both mycobacterial lipids and host lipids, thereby contributing to persistence of the tubercle bacillus inside foamy macrophages (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…LipY was the first PE/PPE protein found to have enzymatic properties, namely triacylglycerol (TAG) lipase activity (Mishra et al, 2008), allowing it to cleave TAG into a diacylglycerol. PE_PGRS35, which contains an aspartic proteinase domain, was shown to be able to process LipY, resulting in the cleavage of the PE domain of LipY, thus may serve as an activation trigger for LipY (Burggraaf et al, 2019; Daleke et al, 2011; Santucci et al, 2019). PE_PGRS10 and PE_PGRS21 are also predicted to be involved in lipid metabolism (Mazandu & Mulder, 2012, Figure 1, Table 1 ) .…”
Section: Pe_pgrs Proteins Promote Mycobacterial Survival Through the mentioning
confidence: 99%